The Important of accounting for throughput and its role in supporting the competitive advantage for Sudanese industrial companies - Ali, Abu baker Ahmed Yousif Mohammed; Ahmed, Shihabeldeen Mohamed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study investigated the important of accounting for throughput and its role in supporting the competitive advantage for Sudanese industrial companies. The problem of the study was that the traditional costing systems not considered accurate in providing information that would help support the competitive advantage in the Sudanese industrial companies. Which lead to look for modern systems، especially the method of accounting for achievement، the study Objectives to clarify the role of the accounting method for achievement in supporting the competitive advantage of Sudanese industrial companies. Accounting for through represents a new method in the field of accounting، as result of the continuous changes in the labor market and intense competition that requires the diversity of products and increasing their quality to continue in competition، the research can be fellow the descriptions analysis methodology. The study results: The method of accounting for throughput works to manage bottlenecks in the production process، which helps in delivering the product in a timely manner، which in turn contributes to supporting the competitive advantage for industrial companies. The study Recommendations: the need to continuing research and study in the tools raised by the method of accounting for throughput and their relationship to the various methods that contribute to supporting competition.